2011
DOI: 10.1208/s12249-011-9622-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Membrane Permeability (PAMPA and Skin) of Benzimidazoles with Potential Cannabinoid Activity and their Relation with the Biopharmaceutics Classification System (BCS)

Abstract: Abstract. The permeability of five benzimidazole derivates with potential cannabinoid activity was determined in two models of membranes, parallel artificial membrane permeability assay (PAMPA) and skin, in order to study the relationship of the physicochemical properties of the molecules and characteristics of the membranes with the permeability defined by the Biopharmaceutics Classification System. It was established that the PAMPA intestinal absorption method is a good predictor for classifying these molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Compounds with Log P values between 1 and 4 have been shown to have ideal liphophilicity and aqueous solubility to penetrate biological membranes. Further, compounds with Log P greater than 4 have been predicted to have poor aqueous solubility and intestinal absorption [30]. Based on this theory, diosgenin is expected to have lower permeability than dioscin, which is in accordance to our observations.…”
supporting
confidence: 89%
“…Compounds with Log P values between 1 and 4 have been shown to have ideal liphophilicity and aqueous solubility to penetrate biological membranes. Further, compounds with Log P greater than 4 have been predicted to have poor aqueous solubility and intestinal absorption [30]. Based on this theory, diosgenin is expected to have lower permeability than dioscin, which is in accordance to our observations.…”
supporting
confidence: 89%
“…The parallel artificial membrane permeation assay (PAMPA) is a method by which the permeability of a substance through a lipid-infused artificial membrane can be determined [12] , [13] . Although there is no active transport in the PAMPA membrane, it is a useful model for predicting the transport behavior of highly lipophilic drug candidates by transcellular absorption.…”
Section: Introductionmentioning
confidence: 99%
“…PAMPA was performed to estimate passive transcellular permeability. PAMPA is a non-cell-based permeability model, but it is considered robust, reproducible, or fast [34][35][36]. It was demonstrated that PAMPA can be used to predict the passive permeability through the gastrointestinal tract of constituents in a complex plant extract [37].…”
Section: Resultsmentioning
confidence: 99%